Photoswitching of Site-Selective RNA Scission by Sequential Incorporation of Azobenzene and Acridine Residues in a DNA Oligomer - Akinori Kuzuya; Keita Tanaka; Makoto Komiyama (Journal of Nucleic Acids)
Photoresponsive systems for site-selective RNA scission have been prepared by combining Lu(III) ions with acridine/azobenzene dual-modified DNA. The modified DNA forms a heteroduplex with substrate RNA, and the target phosphodiester linkages in front of the acridine residue is selectively activated so that Lu(III) ion rapidly cleaves the linkage. Azobenzene residue introduced adjacent to the acridine residue acts as a photoresponsive switch, which triggers the site-selective scission upon UV irradiation. A trans isomer of azobenzene efficiently suppresses the scission, whereas the cis isomer formed by UV irradiation hardly affects the scission. As a result, 1.7–2.4-fold acceleration of the cleavage was achieved simply by irradiating UV for 3 min to the mixture prior to the reaction. Considering the yield of photoisomerization, the intrinsic activity of a cis isomer is up to 14.5-fold higher than that of the trans isomer.